Combined effect of work stress and impaired sleep on coronary and cardiovascular mortality in hypertensive workers: The MONICA/KORA cohort study. (27th April 2019) - Li, Jian; Atasoy, Seryan; Fang, Xioayan; Angerer, Peter; Ladwig, Karl-Heinz
Abstract: Background: Although work stress and impaired sleep are established risk factors for cardiovascular disease (CVD) among healthy individuals, their impact on hypertensive workers is largely unknown. Design: Prospective cohort study design. Methods: Hypertensive workers ( N = 1959), derived from the population-based MONICA/KORA study in Southern Germany, who were free of any cardiovascular disease and diabetes were interviewed at baseline for work stress (high demand plus low control) and impaired sleep (difficulties falling asleep and/or maintaining sleep). Hazard ratios and 95% confidence intervals (CIs) were estimated by multivariate Cox proportional hazards models with adjustment for relevant covariates. Results: During a mean follow-up of 17.8 years covering 34, 900 person-years, 134 fatal CVD and 73 coronary heart disease (CHD) events were observed. In comparison to participants with low work stress and non-impaired sleep, participants with work stress (hazard ratio (HR) 1.56, 95% CI 0.81-2.98), or impaired sleep (HR 1.76, 95% CI 0.96-3.22) had an increased risk of CVD, while participants with both work stress and impaired sleep had the highest risk of CVD mortality (HR 2.94, 95% CI 1.18-7.33). Participants with both risk conditions had an absolute CVD mortality risk of 7.13 cases per 1000 person-years in comparison to 3.05 cases per 1000-person years in the reference group. Similar risk patterns were found for CHD mortality. Conclusions: Our findings add a new piece of evidence that work stress together with impaired sleep increase risk of coronary and cardiovascular mortality in hypertensive workers.